Empowering teachers to screen, guide, and refer schoolchildren with behavioral and mental health problems. A pilot study to promote mental health in Iran - Afshari, Ramin; Kaveh, Mohammad Hossein; Lankarani, Kamran Bagheri; Doolub, Damien; Jaafari, Nematollah; Ostovarfar, Jeyran (Frontiers in Psychiatry, 2022)
Background: Schools are ideal for promoting the mental health of school-age children, but the teachers' current knowledge is insufficient to play an influential role in mental health services at schools. Fortunately, however, teachers have a high sense of responsibility, interest, and talent to receive knowledge and the ability to participate in this field. This study aimed to examine whether a protocol focused on the role of teachers could identify, guide, and care for school-age children with behavioral and mental health problems. Method: The current research was a "before and after" pilot quasi-experimental study conducted in three elementary, secondary, and high schools. The main intervention consisted of a 5-hour workshop based on a ready-to-use booklet for teachers conducted separately in each school. A total of 58 teachers and 872 school-age children were included using a judgmental sampling technique. Results: The pre-and post-workshop mean scores of teachers' knowledge about common mental disorders in school-age children were 6.21 ± 4.58 and 12.50 ± 7.27, respectively. According to the Strength and Difficulty Questionnaire (SDQ), the teachers made 127 referrals, of whom 102 school-age children had problems. Consultants diagnosed 114 school children who reflected 90% of all teachers’ recommendations needing psychological care and counseling. Finally, only 50 diagnosed school-age children were followed up and attended therapy sessions at counseling centers. The sensitivity and specificity of this brief intervention in detecting school-age children with psychological problems were respectively 80.3% and 98.0%. Conclusions: The results of this study support teacher empowerment training's effectiveness in identifying and guiding school-age children needing mental health care. Psychological counseling programs in schools in various quantitative and qualitative dimensions, including responding to school-age children's needs and psychological problems, should be adequately evaluated, and appropriate measures should be taken to promote mental health services. Collaboration between health systems and the education department will increase the effectiveness of mental health programs’ promotion and drug abuse prevention. These pilot data lead the way to designing scientifically sound follow-up studies that will concretely ascertain the benefit of this program.